2016
DOI: 10.1074/jbc.m116.738666
|View full text |Cite|
|
Sign up to set email alerts
|

Bromodomain and Extraterminal Protein Inhibition Blocks Growth of Triple-negative Breast Cancers through the Suppression of Aurora Kinases

Abstract: Bromodomain and extraterminal (BET) proteins are epigenetic "readers" that recognize acetylated histones and mark areas of the genome for transcription. BRD4, a BET family member protein, has been implicated in a number of types of cancer, and BET protein inhibitors (BETi) are efficacious in many preclinical cancer models. However, the drivers of response to BETi vary depending on tumor type, and little is known regarding the target genes conveying BETi activity in triple-negative breast cancer (TNBC). Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 43 publications
7
69
1
Order By: Relevance
“…As an intermediary proof-ofconcept, we recently showed that ALA-PDT suppression of mouse-borne human breast tumor xenografts was substantially augmented by administration of 1400W or GW274150, whereas no significant effect was observed on control tumor growth (52). Consistently, iNOS protein in tumor samples was strongly upregulated after ALA-PDT, and NO-derived NO 2 -levels were also elevated relative to control levels -and in 1400W-inhibitable fashion (53). However, it was apparent from our previous in vitro and in vivo studies that the modulating effects of iNOS enzyme inhibitors (e.g.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…As an intermediary proof-ofconcept, we recently showed that ALA-PDT suppression of mouse-borne human breast tumor xenografts was substantially augmented by administration of 1400W or GW274150, whereas no significant effect was observed on control tumor growth (52). Consistently, iNOS protein in tumor samples was strongly upregulated after ALA-PDT, and NO-derived NO 2 -levels were also elevated relative to control levels -and in 1400W-inhibitable fashion (53). However, it was apparent from our previous in vitro and in vivo studies that the modulating effects of iNOS enzyme inhibitors (e.g.…”
Section: Discussionmentioning
confidence: 50%
“…However, it was apparent from our previous in vitro and in vivo studies that the modulating effects of iNOS enzyme inhibitors (e.g. increased PDT cytotoxicity or decreased survivor aggressiveness) were far from maximal at relatively high inhibitor concentrations or dosages (24)(25)(26)53). This prompted us to ask whether possible suppression of iNOS expression with a BET bromodomain inhibitor such as JQ1 might be more effective than inhibition of expressed iNOS activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA analysis was performed as previously described (12) using the following TaqMan Gene Expression Assays (Thermo Fisher): CCNB1 (Hs01030099_m1); E2F2 (Hs00231667_m1); E2F8 (Hs00226635_m1); FOXM1 (Hs01073586_m1); KIF2C (Hs00901710_m1); KIF20A (Hs00993573_m1); LIN9 (Hs00542748_m1); LIN37 (Hs00375230_m1); MYBL2 (Hs00942543_m1); PLK1 (Hs00983227_m1); GAPDH (Hs02758991_g1).…”
Section: Methodsmentioning
confidence: 99%
“…We and others have recently reported that bromodomain and extraterminal protein inhibitors (BETi) are efficacious in multiple models of TNBC (913). We further discovered that BETi induce the formation of large, multinucleated cells followed by apoptosis and senescence, suggesting these drugs cause mitotic catastrophe (12). BETi selectively target the BET family of epigenetic readers by binding to the bromodomain pockets of BET proteins (BRD2, BRD3, BRD4, and BRDT).…”
Section: Introductionmentioning
confidence: 97%